An emerging technology in lipid research for targeting hydrophilic drugs to the skin in the treatment of hyperpigmentation disorders: kojic acid-solid lipid nanoparticles - Khadijeh Khezri; Majid Saeedi; Katayoun Morteza-Semnani; Jafar Akbari; Seyyed Sohrab Rostamkalaei (Artificial Cells, Nanomedicine, and Biotechnology, 2020)
Kojic acid (KA) as tyrosinase inhibitor shows insufficient skin penetration and several adverse events due topical administration. KA solid lipid nanoparticles (KA-SLNs) were prepared using high speed homogenisation followed by ultra-probe sonication method for improve its effectiveness.KA-SLNs was optimised by Glyceryl mono-stearate (GMS) and Cholesterol (Chol) as lipid excipients and span 60 (SP 60) and Tween 20 (Tw 20) as co-emulsifiers (particle size 156.97 ± 7.15 nm, encapsulation efficiency 59.02 ± 0.74%, drug loading 14.755 ± 1.63%, polydispersity index (PDI) of 0.388 ± 0.004 and zeta potential (ZP) of -27.67 ± 1.89 mV). Optimum formulation (KA-SLN3 dispersion) was stable at 4 and 25 °C for 3 months. Also, TEM image confirmed these results. The results of XRD, DSC and ATR-FTIR analysis indicated that KA was well encapsulated within the SLNs either in molecularly dispersed state and stabilised in amorphous form and there was no chemical interaction between drug and other ingredients. Controlled release was achieved with this formulation. KA-SLN3 dispersion have more tyrosinase inhibition potency in comparison with pure KA. Also, the results of the ex vivo and in vitro percutaneous absorption show that KA-SLN3 dispersion improved percutaneous delivery of KA as a promising and potential novel topical preparation and might open new avenues for treatment of hyperpigmentation disorders.